Strukturelle Evolution des Signalerkennungspartikels$aRNA in der Proteinzielsteuerung - Kempf, Georg; Wild, Klemens; Sinning, Irmgard (Biospektrum, 2015)
The signal recognition particle (SRP) is a ribonucleoprotein complex, which plays a central role in the first steps of membrane protein and secretory protein biogenesis. It recognizes nascent polypeptides at the ribosome by an N-terminal signal sequence and guides them to the translocation channel in the membrane of the endoplasmatic reticulum in eukaryotes, or the cell membrane in prokaryotes. Here, we focus on recent structural insights highlighting the SRP RNA as a dynamic module and on evolutionary aspects of RNA to protein transitions.